Investigation of the Performance of the Disintegration Test for Dietary Supplements - Almukainzi, May (Springer US, 2010)
The aim of this study was to investigate how beaker size, basket assembly, use of disk, and immersion medium impact the disintegration time of dietary supplements. The disintegration times were determined for five tablet and two capsule products. A two-station disintegration tester was used with Apparatus A or Apparatus B as described in the United States Pharmacopeia (USP) chapters, <701> and <2040>. Two beakers complying with the harmonized specifications were used, one with a volume of 1,000 mL and one with a 1,500-mL volume. The disintegration data were analyzed using ANOVA for the following factors: beaker size, equipment (App A and B) and condition (with/without disk). Two tablet products were not sensitive to any changes in the test conditions or equipment configurations. One product was only partially sensitive to the test conditions. The other products showed impact on the disintegration time for all test conditions. The results revealed that these tablet products might pass or fail current USP disintegration requirements depending on the equipment configuration. Similar results were obtained for the two investigated capsule formulations. One product might fail current USP disintegration requirements if the large beaker was used, but might pass the disintegration requirements when the small beaker was used. Hydroxy propyl methyl cellulose capsules were mostly influenced if sodium instead of a potassium buffer was used as the immersion medium. The results demonstrate that the current harmonized ICH specifications for the disintegration test are insufficient to make the disintegration test into reliable test for dietary supplements.